Purchase Intention Through Social Media Commerce with Age and Gender as Moderating Variables: An Empirical Study - Paramitha, Nabilla; Havidz, Ikramina Larasati Hazrati (Majalah Ilmiah Bijak, 2023)
Purchase intention helps entrepreneurs to decide where the geographic market is and how to segment the customers where the products and services are sold on social commerce media. The aim of this studyto be able to find out empirically about the influence of attitude, ease of use, perceived usefulness, on purchase intention through social commerce media which is moderated by gender and ageThis research was conducted in early July - late July 2023. The data collection process was carried out by distributing questionnaires online in the form of Google forms. This research was conducted on 125 Tiktok social media users in Indonesia. The data obtained was analyzed usingmethodPartial Squares Structural Equation Modeling(PLS-SEM). The results of this research show that attitude has a positive and significant effect on purchase intention. Next, ease of use has a positive and significant effect on purchase intention. Then, perceived usefulness has a positive and insignificant effect on purchase intention. Furthermore, young age has no influence on the relationship between ease of use and purchase intention. Next, women have no influence on perceived usefulness and it is not significant on purchase intention.